1989
DOI: 10.1016/0014-5793(89)81079-8
|View full text |Cite
|
Sign up to set email alerts
|

Internal amino acid sequence analysis of the 80 kDa protein kinase C substrate from rat brain: Relationship to the 87 kDa substrate from bovine brain

Abstract: We have obtained sequence data from five proteolytic peptides totalling 102 amino acid residues of the 80 kDa protein kinase C substrate purified from rat brain. The amino acid sequences of these five peptides were compared with that deduced from a cDNA encoding the 87 kDa protein kinase C substrate from bovine brain. The overall amino acid sequence identity within the regions covered by our peptides is 54%. Two peptides aligned at the C-and N-termini of the bovine protein kinase C substrate with a very high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the 80 kDa PKC substrate from Swiss 3T3 fibroblasts is heat stable [ 18,191, Therefore, a purification scheme involving heat treatment, DEAE-cellulose chromatography, G-l 50 gel filtration and electroelution from preparative SDS polyacrylamide gels was followed as previously described for the purification of the rat brain protein [19,24]. Approximately 10 lug of homogeneous 80 kDa protein was isolated from the cytosolic fraction of 2.3 x 10" confluent, quiescent Swiss 3T3 fibroblasts (Table I).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the 80 kDa PKC substrate from Swiss 3T3 fibroblasts is heat stable [ 18,191, Therefore, a purification scheme involving heat treatment, DEAE-cellulose chromatography, G-l 50 gel filtration and electroelution from preparative SDS polyacrylamide gels was followed as previously described for the purification of the rat brain protein [19,24]. Approximately 10 lug of homogeneous 80 kDa protein was isolated from the cytosolic fraction of 2.3 x 10" confluent, quiescent Swiss 3T3 fibroblasts (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…2. The amino acid sequences of peptides A-E1 of the Swiss 3T3 fibroblast 80 kDa protein were aligned with the deduced amino acid sequence of the bovine brain 87 kDa PKC substrate [23] and with proteolpic peptides from the rat brain 80 kDa PKC substrate [24] (unpublished data). Vertical lines between amino acids denote identical residues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations